Metabolic Reprogramming in Prostate Cancer: Impact of TP53 Gain-of-Function Mutations on Tumor Progression and Therapeutic Vulnerabilities - Usman, Farida Jazuli; Gupta, Dikshat Gopal; Abdulkadir, Sarki A; Usman, Ibrahim Muhammad; Alhassan, Adamu Jibrin; Yoo, Young A; Bello, Haris Jaafar; Kurfi, Binta G.; Babagana, Kamaluddeen (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Prostate cancer (PC) is one of the most common malignancies affecting men worldwide, and androgen hormone deprivation therapy (ADT) serves as an effective first-line treatment, inducing favorable responses in advanced PC patients. Despite advancements in the treatment of advanced prostate cancer, including metastatic castration-resistant prostate cancer (mCRPC), the disease remains lethal, often developing resistance to conventional therapies such as androgen deprivation therapy (ADT) and chemotherapy. Therapy resistance poses a significant challenge, particularly in aggressive forms of prostate cancer. Data on TP53 mutations, especially gain-of-function (GOF) mutations, and their specific impact on prostate cancer metabolism remain limited, underscoring the need for a deeper understanding to uncover new therapeutic avenues. This study aimed to explore the metabolic consequences of TP53 GOF mutations (R175H and R273H) in prostate cancer progression using metabolomics analysis. Approximately 300 metabolites were significantly altered across PC3-GFP (KO), PC3-TP53WT (WT), and PC3-TP53 mutant (R175H & R273H) models. Key findings revealed dysregulation of essential metabolites, such as \(α\)-ketoglutarate and spermidine, which support cancer cell survival and progression. These insights not only enhance the understanding of the interplay between TP53 mutations and metabolic alterations but also identify potential biomarkers for prognosis and therapeutic targeting in therapy-resistant prostate cancer. In the TP53-R175H mutant, numerous essential metabolites were dysregulated (downregulated: glutamine, GAP/DHAP, and \(α\)-ketoglutarate; Upregulated: deoxyuridine, spermidine, and pseudouridine) when compared with the control (KO), thereby causing metabolic shifts that favor cancer cell survival. Conversely, metabolites such as GlaNAC/GlcNAC, adenosine, acetoacetic acid, acetylcholine, octopamine, itaconic acid, lactic acid, and NADP+ are all downregulated in the R273H mutant. While spermine, spermidine, N-acetyl-DL-serine, pseudouridine, deoxyguanosine, sucrose, and AMP/dGMP are upregulated by the R273H mutant but downregulated in GFP (KO). These findings showed that TP53 GOF mutations (R175H & R273H) cause metabolic alterations in numerous metabolites essential for tumor survival and progression. Furthermore, it may provide therapeutic benefits by identifying appropriate biomarkers that could be used as diagnostic and/or prognostic tools for prostate cancer. Future studies should focus on elucidating the distinct metabolic roles of each TP53 mutant, employing advanced techniques such as isotope tracing to track metabolic fluxes in real time. Additionally, therapeutic strategies targeting polyamine metabolism, redox imbalance, and TCA cycle disruptions could provide novel avenues for treatment, particularly for therapy-resistant prostate cancers.